KINERJA DINAS KEBERSIHAN DAN PERTAMANAN DALAM IMPLEMENTASI KEBIJAKAN PENGELOLAAN KEBERSIHAN DI KOTA MANADO - RAKIAN, RESSY (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRAK : Under Regulation No. Manado City . 04 of 2008 that the Department of Hygiene and Manado City is implementing elements of success in the field of regional autonomy and landscaping to perform basic tasks in the field of local government affairs cleanliness and landscaping . In carrying out this task then set policies ( programs and activities ) , among others, is in the field of hygiene management . Issues to be addressed in this study is how the performance of the organization and Sanitation Department Manado City in hygiene management policy implementationThe research method used was a qualitative method . Levels of organizational performance seen from three aspects , namely : ( 1 ) effectiveness , ie whether hygiene management policies that have been defined and implemented to achieve planned performance targets , (2 ) efficiency , ie whether the resources used by the organization to achieve the best possible results , and ( 3 ) Responsiveness , ie whether the problems that arose related to the implementation of hygiene management tasks can be solved quickly and effectively . Data sources / informants consisted of 15 people consisting of structural and operating staff employees at the Department of Sanitation and the city of Manado . Collecting data using interview techniques . Analysis of data using qualitative analysis techniques interactive modelBased on the results of the study conclude : ( 1 ) Performance Department in the implementation of hygiene management policy effectiveness from the aspects already showed a good level / high , (2 ) performance management policy of the Department in the implementation of hygiene from the aspects efficient use of budgetary and human resources are better / high , but in the use of infrastructure / facilities ( equipment ) is less efficient , and ( 3 ) Performance Department in the implementation of hygiene management policies seen from the aspect of responsiveness showed a good level / high .Conclusions based on these results it is necessary that the suggestions put forward to improve the performance of services in the management of hygiene need additional facilities such as garbage collection carts , trash bins and countainer , and facilities / infrastructure management of sanitation / solid waste such as garbage trucks and cars for structuring ekscavator landfill . Also needs to be done or improved cooperation with the private sector in the management or other staholders cleanliness of the city .Keywords: performance, policy implementation, management of hygiene.